2010
DOI: 10.1016/s1734-1140(10)70256-5
|View full text |Cite
|
Sign up to set email alerts
|

Scavenging and antioxidant potential of physiological taurine concentrations against different reactive oxygen/nitrogen species

Abstract: While several studies have been conducted on the antioxidant properties of the beta-amino acid taurine, these studies all used concentrations lower than what is found physiologically. This study investigates the scavenging and antioxidant properties of physiological taurine concentrations against different reactive species. No reactivity between taurine and hydrogen peroxide was found; however, taurine exhibited significant scavenging potential against peroxyl radical, nitric oxide, and superoxide donors. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
78
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(88 citation statements)
references
References 41 publications
6
78
0
1
Order By: Relevance
“…Dietary taurine supplementation increased SOD activities in the free range hens. These results are consistent with several other studies showing that taurine has an anti-oxidant role (Lakshmi Devi and Anuradha, 2010;Oliveira et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Dietary taurine supplementation increased SOD activities in the free range hens. These results are consistent with several other studies showing that taurine has an anti-oxidant role (Lakshmi Devi and Anuradha, 2010;Oliveira et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…However, taurine did protect normal rat liver cells against isoniazid and hydrazineinduced toxicity. These protective effects are associated with the scavenging of free radicals and prevention of GSH depletion (29,30), which might explain why it was not as effective in glutathione- depleted cells. Another reason for its ineffectiveness in glutathione-depleted cells is that the duration of treatment with taurine was not suffi cient to upregulate antioxidant enzymes in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that taurine is a very stable molecule, it may have a scavenger-type role against reactive oxygen species (ROS). In fact, it has been demonstrated that taurine inhibits lipoperoxidation induced by tert-butyl hydroperoxide in slices of rat liver and can protect thiol groups from oxidation [38].…”
Section: Discussionmentioning
confidence: 99%